PopIII signatures in the spectra of PopII/I GRBs. Issue 3 (8th April 2015) - Ma, Q.; Maio, U.; Ciardi, B.; Salvaterra, R.
Abstract : We investigate signatures of Population III (PopIII) stars in the metal-enriched environment of gamma-ray bursts (GRBs) originating from Population II-I (PopII/I) stars by using abundance ratios derived from numerical simulations that follow stellar evolution and chemical enrichment. We find that at z  > 10 more than 10 per cent of PopII/I GRBs explode in a medium previously enriched by PopIII stars (we refer to them as GRBII→III). Although the formation of GRBII→III is more frequent than that of pristine PopIII GRBs (GRBIIIs), we find that the expected GRBII→III observed rate is comparable to that of GRBIIIs, due to the usually larger luminosities of the latter. GRBII→III events take place preferentially in small protogalaxies with stellar masses M ⋆ ∼ 10 4.5 -10 7  M⊙, star formation rates $\rm SFR \sim 10^{-3}{\rm -}10^{-1}\, \rm M_{\odot }\, yr^{-1}$ and metallicities Z ∼ 10 − 4 -10 − 2  Z⊙ . On the other hand, galaxies with Z < 10 − 2.8  Z⊙ are dominated by metal enrichment from PopIII stars and should preferentially host GRBII→III. Hence, measured GRB metal content below this limit could represent a strong evidence of enrichment by pristine stellar populations. We discuss how to discriminate PopIII metal enrichment on the basis of various abundance ratios observable in the spectra of GRBs' afterglows. By employing such analysis, we conclude that the currently known candidates at redshift z ≃ 6 – i.e. GRB 050904 and GRB 130606A – are likely not originated in environments pre-enriched by PopIII stars. Abundance measurements for GRBs at z ≃ 5 – such as GRB 100219A and GRB 111008A – are still poor to draw definitive conclusions, although their hosts seem to be dominated by PopII/I pollution and do not show evident signatures of massive PopIII pre-enrichment.